Analisis Relasi Antara Keberfungsian Keluarga dan Kontrol Diri pada Remaja di Aceh Tamiang - Zuhra, Asmaur Ridhana; Nisa, Haiyun (Psikoislamedia: Jurnal Psikologi, 2018)
Adolescents are a group of individuals who are in a transitional period with a tendency to be irritable and difficult to control emotions however deviant behavior that becomes a form of juvenile delinquency. One of the factors causing delinquency and deviant behavior in adolescents is low self-control and families that is not functioning effectively. Self-control is the ability of individuals to decide their behavior based on certain standards such as morals, values, and rules in the community to lead to positive behavior, although family functioning is interaction in the family that affects the physical and emotional health of family members. This study aims to determine the dynamics of the relationship between family functioning and self-control in adolescents in Aceh Tamiang. Respondents in this study amounted to 360 young men and women who lived in Aceh Tamiang which was obtained by the disproportional stratified random sampling method. Data analysis using Pearson Product Moment correlation technique. The result of the correlation coefficient (r) is - 0.228 with a value of p = 0.000 (p <0.05). This shows that there is a significant relationship between family functioning and self-control in adolescents. The more effective the functioning of the family, the higher the self-control that is owned by Adolescents.